TAL effectors and the executor R genes - Zhang, Junli; Yin, Zhongchao; White, Frank (Frontiers in Plant Science, 2015)
Transcription activation-like (TAL) effectors are bacterial type III secretion proteins that function as transcription factors in plants during Xanthomonas/plant interactions, conditioning either host susceptibility and/or host resistance. Three types of TAL effector associated resistance (R) genes have been characterized - recessive, dominant non-transcriptional and dominant TAL effector-dependent transcriptional based resistance. Here, we discuss the last type of R genes, whose functions are dependent on direct TAL effector binding to discrete effector binding elements in the promoters. Only five of the so-called executor R genes have been cloned, and commonalities are not clear. We have placed the protein products in two groups for conceptual purposes. Group 1 consists solely of the protein from pepper, BS3, which is predicted to have catalytic function on the basis of homology to a large conserved protein family. Group 2 consists of BS4C-R, XA27, XA10, and XA23, all of which are relatively short proteins from pepper or rice with multiple potential transmembrane domains. Group 2 members have low sequence similarity to proteins of unknown function in closely related species. Firm predictions await further experimentation on these interesting new members to the R gene repertoire, which have potential broad application in new strategies for disease resistance.